Cervical Internal Carotid Artery Saccular Aneurysm Manifesting with Progressive Dysphonia - Cardoso, Arquimedes Cavalcante; Marques Júnior, Marcos Alcino Soares Siqueira; Marques, Marcos Alcino Soares Siqueira; Lemos, Luiz Eurípedes Almondes Santana; Moura, Samuel Ricardo Batista; Marques, Amanda Mendonça; Lima, Laysa Layna Ribeiro; Macedo, Lívio Pereira de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2015)
Aneurysm of the cervical internal carotid artery is a rare condition, which can trigger severe neurologic complications. The authors report a case of a female patient of 54 years, presenting as a progressive dysphonia, which revealed it to be an aneurysm of the extracranial portion of the internal carotid artery. Endovascular treatment was used.
Keywords: Internal carotid artery; aneurysm; dysphonia